Answer:
0.942
Step-by-step explanation:
Multiply the normal way as if there were no decimals, then move the decimal 3 times to the left.
Answer:
Step-by-step explanation:
Hypotenuse² =base² + altitude²
(3x + 4)² = (2x + 1)² + (3x)²
{Use (a+b)² = a² + 2ab + b²}
(3x)² + 2*3x+4 + 4² = (2x)² + 2*2x*1 + 1² + 9x²
9x² + 24x + 16 = 4x² + 4x + 1 + 9x²
9x² + 24x + 16 = 13x² + 4x + 1
0 = 13x² + 4x + 1 - 9x² - 24x - 16
13x² - 9x² + 4x - 24x +1 - 16 = 0
4x² - 20x - 15 = 0
a = 4 ; b =-20 ; c = -15
D = b² - 4ac = (-20)² - 4*4*(-15) = 400 + 240 = 640
√D = √640 = 25.30
![x=\dfrac{-b+\sqrt{D}}{2a} \ ; \ x=\dfrac{-b-\sqrt{D}}{2a}\\\\\\x=\dfrac{20+25.30}{2*4} \ ; \ x=\dfrac{20-25.30}{2*4}\\\\\\x=\dfrac{45.30}{8} \ ; \ x =\dfrac{-5.30}{8}\\\\](https://tex.z-dn.net/?f=x%3D%5Cdfrac%7B-b%2B%5Csqrt%7BD%7D%7D%7B2a%7D%20%5C%20%3B%20%5C%20x%3D%5Cdfrac%7B-b-%5Csqrt%7BD%7D%7D%7B2a%7D%5C%5C%5C%5C%5C%5Cx%3D%5Cdfrac%7B20%2B25.30%7D%7B2%2A4%7D%20%5C%20%3B%20%5C%20x%3D%5Cdfrac%7B20-25.30%7D%7B2%2A4%7D%5C%5C%5C%5C%5C%5Cx%3D%5Cdfrac%7B45.30%7D%7B8%7D%20%5C%20%3B%20%5C%20%20x%20%3D%5Cdfrac%7B-5.30%7D%7B8%7D%5C%5C%5C%5C)
x = 5 .66 ; x = -0.66
Ignore x = -0.66 as length of a side cannot be negative
Answer : x = 5.66
Treat the matrices on the right side of each equation like you would a constant.
Let 2<em>X</em> + <em>Y</em> = <em>A</em> and 3<em>X</em> - 4<em>Y</em> = <em>B</em>.
Then you can eliminate <em>Y</em> by taking the sum
4<em>A</em> + <em>B</em> = 4 (2<em>X</em> + <em>Y</em>) + (3<em>X</em> - 4<em>Y</em>) = 11<em>X</em>
==> <em>X</em> = (4<em>A</em> + <em>B</em>)/11
Similarly, you can eliminate <em>X</em> by using
-3<em>A</em> + 2<em>B</em> = -3 (2<em>X</em> + <em>Y</em>) + 2 (3<em>X</em> - 4<em>Y</em>) = -11<em>Y</em>
==> <em>Y</em> = (3<em>A</em> - 2<em>B</em>)/11
It follows that
![X=\dfrac4{11}\begin{bmatrix}12&-3\\10&22\end{bmatrix}+\dfrac1{11}\begin{bmatrix}7&-10\\-7&11\end{bmatrix} \\\\ X=\dfrac1{11}\left(4\begin{bmatrix}12&-3\\10&22\end{bmatrix}+\begin{bmatrix}7&-10\\-7&11\end{bmatrix}\right) \\\\ X=\dfrac1{11}\left(\begin{bmatrix}48&-12\\40&88\end{bmatrix}+\begin{bmatrix}7&-10\\-7&11\end{bmatrix}\right) \\\\ X=\dfrac1{11}\begin{bmatrix}55&-22\\33&99\end{bmatrix} \\\\ X=\begin{bmatrix}5&-2\\3&9\end{bmatrix}](https://tex.z-dn.net/?f=X%3D%5Cdfrac4%7B11%7D%5Cbegin%7Bbmatrix%7D12%26-3%5C%5C10%2622%5Cend%7Bbmatrix%7D%2B%5Cdfrac1%7B11%7D%5Cbegin%7Bbmatrix%7D7%26-10%5C%5C-7%2611%5Cend%7Bbmatrix%7D%20%5C%5C%5C%5C%20X%3D%5Cdfrac1%7B11%7D%5Cleft%284%5Cbegin%7Bbmatrix%7D12%26-3%5C%5C10%2622%5Cend%7Bbmatrix%7D%2B%5Cbegin%7Bbmatrix%7D7%26-10%5C%5C-7%2611%5Cend%7Bbmatrix%7D%5Cright%29%20%5C%5C%5C%5C%20X%3D%5Cdfrac1%7B11%7D%5Cleft%28%5Cbegin%7Bbmatrix%7D48%26-12%5C%5C40%2688%5Cend%7Bbmatrix%7D%2B%5Cbegin%7Bbmatrix%7D7%26-10%5C%5C-7%2611%5Cend%7Bbmatrix%7D%5Cright%29%20%5C%5C%5C%5C%20X%3D%5Cdfrac1%7B11%7D%5Cbegin%7Bbmatrix%7D55%26-22%5C%5C33%2699%5Cend%7Bbmatrix%7D%20%5C%5C%5C%5C%20X%3D%5Cbegin%7Bbmatrix%7D5%26-2%5C%5C3%269%5Cend%7Bbmatrix%7D)
Similarly, you would find
![Y=\begin{bmatrix}2&1\\4&4\end{bmatrix}](https://tex.z-dn.net/?f=Y%3D%5Cbegin%7Bbmatrix%7D2%261%5C%5C4%264%5Cend%7Bbmatrix%7D)
You can solve the second system in the same fashion. You would end up with
![P=\begin{bmatrix}2&-3\\0&1\end{bmatrix} \text{ and } Q=\begin{bmatrix}1&2\\3&-1\end{bmatrix}](https://tex.z-dn.net/?f=P%3D%5Cbegin%7Bbmatrix%7D2%26-3%5C%5C0%261%5Cend%7Bbmatrix%7D%20%5Ctext%7B%20and%20%7D%20Q%3D%5Cbegin%7Bbmatrix%7D1%262%5C%5C3%26-1%5Cend%7Bbmatrix%7D)
Answer:
What question '='
Step-by-step explanation:
Answer:
B
Step-by-step explanation:
11.3+4.2=15.5m to the nearest tenth